Attractiveness of a City as a Factor of Territorial Mobility in Student Estimates (on the Example of Ekaterinburg) - S. B. Abramova; N. L. Antonova; O. I. Pimenova (Russian State Vocational Pedagogical University, 2019)
Introduction. The attractiveness of the city as a place to live and fulfill needs becomes one of the determining factors for the intensification of territorial mobility among young people. The image of the city and the image of the "future" are closely related and interdependent in consciousness of young people. Megalopolis as a high-resource territory is a special space for the implementation of students' life plans. Hence, it is important to pay special attention to students as a potential driver for the development of the territory (city, region, country), creating an attractive urban environment.Aim. Taking into account the results of a sociological study, the aims of the publication were the following: to analyse the attractiveness of the city, to characterise its place in the life planning of students and to determine the role in territorial movements.Methodology and research methods. The empirical basis of the study was a semi-standardised questionnaire for students of 3-4 courses at 9 universities in Ekaterinburg (n = 200), and in-depth interviews with students representing different types of orientations to territorial mobility (n = 8). Collected data were processed by means of a method of thematic networks.Results and scientific novelty. According to respondents, the factors, which provide comfort of life in the city, are considered; competitive advantages and shortcomings of the environment of the megalopolis are characterised; it is shown how its specific characteristics are reflected in vital plans of students. Two idealised ideas of the city as the place for life are allocated: 1) a "comfortable" city for everyday practices and open for innovations and creativity; 2) an "instrumental" city as the platform for career development and material welfare, which can be emotionally unattractive, but functionally effective. The factor constraining territorial mobility is the reproduction of social connections and relations in the current residence area; students view the movement as a type of risky behaviour. However, 42% of respondents include in their life plans a move to another city, located both in Russia and abroad. In the motivational structure of territorial mobility, the leading positions are occupied by the desire for independence, the idealised image of the city planned for life, and the discrepancy between the conditions of a particular city and the actual needs of the young generation. Hence, the strategic direction of planning and designing urban space is the increase in the socio-cultural, economic, and environmental sustainability of the territory. Administrative structures as the agents, initiating, introducing and regulating the complex strategy of increase in attractiveness of the territory, need to consider not only the territorial capital, which the megalopolis has, but also typical needs and interests of the target social groups, especially those related to the creative class.Practical significance. The presented materials and the authors' conclusions can be used to determine the priority directions of the development of urban environment and intra-urban youth policy and to develop programmes for forming students' competencies related to life planning and territorial mobility.